Kejadian Karies Gigi pada Tenaga Kesehatan di Rumah Sakit - Puspita, Eka; Gustina, Ema; Ekawati, Dianita; Rahutami, Synthia (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background: Dental caries is a disease that is most commonly found in the oral cavity along with periodontal disease, which occurs due to demineralization of tooth surface tissue by acids produced by orgnanisms in the mouth that interact with food waste containing sugar. Its development requires a long period of time so that many sufferers are at risk of potentially lifelong disorders. The DMF-T index shows the number and level of tooth decay, which is measured using the sum of untreated cavities or caries (D), the number of teeth that have been extracted and missing teeth (M) and the number of teeth filled (F). The aims of tis study was to analyze the incidence of dental caries among health workers in hospitals. Method: this research uses a quantitative type with a descriptive analytical design using a cross sectional method. This research was carried out in February-March 2024 at Sungai Lilin Hospita, Musi Banyuasin Regency. The population in this study were health workers at Sungai Lilin Hospital in 2024 with a sample of 183 people taken using total sampling technique. Results: Data analysis was carried out univariate and bivariate using the chi-square with α=0,05. The research results showed that the knowledge variable p value = 0,011 with an OR = 2,625, frequency of tooth brushing p value = 0,000 with an OR = 8,067 and tooth brushing technique p value = 0,000 with an OR = 4,454 on the incidence of dental caries in health workers in hospitals. Conclusion: The conclusion of the research was that there was a relationship between knowledge, frequency of tooth brushing technique with the incidence of dental caries among health workers in hospitals.